Cerebral embolism and carotid-hyoid impingement syndrome. (June 2019) - Kho, Lay Kun; Bates, Timothy R; Thompson, Andrew; Dharsono, Ferry; Prentice, David
Highlights: Embolic stroke of undetermined source is not uncommon in young patients. We describe embolic strokes from carotid artery injury secondary to hyoid bone impingement. Following resection of the greater cornu of the hyoid bone, the patients had no further strokes. Abstract: Embolic stroke of undetermined source (ESUS) is not uncommon in young patients. Here, we describe two cases of stroke from an unusual aetiology; cerebral embolization from carotid artery injury presumed secondary to hyoid bone impingement. Both patients demonstrated angiographic evidence of hyoid bone impingement. Following resection of the greater cornu of the hyoid bone, neither patient had further strokes.